Personalized Cup Positioning Guides Improved Cup Positioning and Hip Ranges of Motion in Robotic Assisted Total Hip Arthroplasty - Wang, Ruoyu; Zheng, Xiaojing; Xu, Tianze; Gong, Song; Liu, Shaokai; Han, Lizhi; Yang, Shuhua; Xu, Weihua (Frontiers in Bioengineering and Biotechnology, 2020)
Objective Precise hip cup positioning is essential for the prevention of component impingement and dislocation in robotic assisted total hip arthroplasty (THA). Currently, the robotic system uses a mechanical alignment guide (MAG) for cup placement, which is one-size-fits-all, and the optimal cup positioning is controversial. Robotic assisted THA has not used any personalized cup positioning guides. The goal of this study was to identify an optimal guide for cup placement in robotic assisted THA to improve prognosis and life quality after THA. Materials and Methods Pelvis and femoral CT data of 47 participants were retrospectively collected for preoperative planning of robotic THA. The universal MAG guide and three personalized guides, including acetabular rim labrum guide (ARLG), transverse acetabular ligament guide (TALG), and ischiatic-pubis line guide (IPLG), were used to pose cups in the acetabulum of each participant. The position of cups was evaluated by inclination and anteversion; the function of hip joints was evaluated by hip ranges of motion, including abduction, adduction, extension, flexion, internal rotation, and external rotation. Results In terms of cup positioning, ARLG provided a bigger cup inclination (p < 0.0001), while IPLG and TALG provided smaller cup inclination (p < 0.001) than MAG; the three personalized guides provided larger cup anteversion (p < 0.0001) than MAG. In terms of HROMs, compared with the use of MAG, the use of three personalized guides significantly decreased abduction (p < 0.0001), extension (p < 0.0001), and external rotation (p < 0.0001), but increased significantly flexion (p < 0.0001) and internal rotation (p < 0.0001); the use of ARLG significantly reduced adduction (p < 0.0001), but the use of IPLG and TALG increased adduction (p < 0.0001). Conclusion Compared with MAG, personalized guides provided greater flexion and internal rotation, which may reduce the risk of posterior dislocation. Among the three personalized guides, IPLG is the most reliable one for the preoperative planning of robotic assisted THA.